2022
DOI: 10.1590/1980-5373-mr-2021-0173
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Morphological Changes and the Growth Kinetics of the Oxides Formed by the High Temperature Oxidation of Cu-32.02% Zn-2.30% Pb Brass

Abstract: The high temperature oxidation of Cu-32.02% Zn-2.30%Pb brass was carried in N 2 -5wt.% O 2 and N 2 -12 wt.% O 2 atmospheres. The amounts of oxygen in the oxidizing atmospheres and the time of the oxidation affected the oxide morphologies and kinetics of the oxide growth. In the first hour of the oxidation at 650 °C, oxide nanowires were noted. The average diameter, length and distance between the observed nanowires were 27 ± 0.01 nm, 0.20 ± 0.04 µm and 0.20 ± 0.04 µm respectively for the samples oxidized in N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The two different materials of copper and zinc are grown into each other with a specific thickness in an alternative layer in the superlattice structure. The XRD pattern with As a result, the low brass structure is found to be appropriately described as a superlattice structure [67].…”
Section: Discussion Of Ordered-disordered Transitional States Of the ...mentioning
confidence: 96%
See 1 more Smart Citation
“…The two different materials of copper and zinc are grown into each other with a specific thickness in an alternative layer in the superlattice structure. The XRD pattern with As a result, the low brass structure is found to be appropriately described as a superlattice structure [67].…”
Section: Discussion Of Ordered-disordered Transitional States Of the ...mentioning
confidence: 96%
“…The d of about 10 nm thickness indicated the typical thickness of the superlattice structure that was made up of alternative layers of two different materials[66]. As a result, the low brass structure is found to be appropriately described as a superlattice structure[67].…”
mentioning
confidence: 97%
“…In any case, the treatment of nickel, cobalt, or copper tubes with oxygen atoms causes oxidation and the oxides are rarely in the form of a smooth film of uniform thickness. Many authors reported very rich morphology after treating metallic samples with oxygen plasma [66][67][68]. The evolution of surface morphology depends on numerous parameters, but it is clear that the morphology evolves with increasing treatment times.…”
Section: Co 3 Omentioning
confidence: 99%
“…The oxide layer formed was found to be convoluted. Such convolution is essentially due to the difference in the thermal expansivity, both in linear and volumetric terms, of the Cu-32.02% Zn-2.30% Pb alloy substrate and the oxides formed [19].…”
Section: The Surface Morphology After the Thermal Oxidationmentioning
confidence: 99%